On the elastoplastic stability problem of the thin round cylindrical shells subjected to complex loading processes with the various kinematic boundary conditions - Dung, Dao Van (Vietnam Journal of Mechanics, 2004)
In this paper, the elastoplastic stability of cylindrical shells simultaneously subjected to compression force along the generatrix and external pressure has been presented. Two types of considered kinematic boundary conditions are simply supported and clamped at the butt-ends. The expressions for determining the critical forces by using the Bubnov-Galerkin method [3] have been established. The sufficient condition of extremum for a long cylindrical shell also is considered. Some results of numerical calculation have been also given and discussed.